A gameficação como metodologia para ensinar e aprender a história do Maranhão republicano no 6º e 7° ano do ensino fundamental: manual de experiências - FERREIRA, Diogo Rogério Martins (2024)
It is proposed to use gamification as a tool in teaching History, particularly Elementary Education, with the aim of obtaining student engagement and improving teaching and youth learning. The proposal seeks to enhance the teaching and learning of History of Maranhão Republican as a working model that can be replicated in other school contexts as well as in other areas of knowledge with changes and adaptations that are necessary. We start from the teaching experience we already have with a view to the strict-sensu professional master's program, seeking to place the experience of educational games in a classroom context in an epistemological approach that encompasses notions of politics and citizenship. Thus, the problem is centered on a methodological strategy adopted in the field of Gamification when it involves the use of games in the classroom with the purpose of creating a teaching and learning environment mediated by collaboration, interaction and challenges, in addition to entertainment. To this end, a Gamefied structure anchored in the theme will be used, aiming to develop the cognitive skills of students with a view to collaborative learning recorded in the Experience Manual.